Analisis Desain Kemasan Teh Cikarau - Muhamad Ilham; Defri Rahman; Hanafi Malik; Juwita Wirta Sri Depi; Ahmad Fachri; Nuraisyah NST (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The appeal of a product is undoubtedly linked to its packaging design. The packaging design serves as the primary identity that distinguishes a product from other similar products. This study aims to analyze the packaging design of Cikarau Tea, a product developed by students of the Agribusiness Study Program at Adzkia University, using theories of visual and practical appeal. This study uses a qualitative method that provides descriptive data on packaging design and its information that is in line with the theory and visual literature used. Data collection was carried out through observation and interview stages. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The result of this study is a visual analysis of Cikarau Tea packaging as an academic reference that can be useful for designers and business people who will make similar products